ESTIMATION OF SOCIETY ECONOMIC COSTS DUE TO FLOODS - Sulistya Rini Pratiwi; Meylin Rahmawati; Kartini Kartini (Journal of Applied Economics in Developing Countries, 2022)
The purpose of this study is to estimate the value of economic losses due to river floods and interpret the perceptions of the affected community on flood risk. This study uses a descriptive analysis method to look at people's perceptions as a result of flooding and uses the actual market price approach, cost of time, and Human Capital Approach to measure how much the estimated value of losses due to flooding is in the Sembakung District area. Community economic losses are calculated based on direct losses and indirect losses. The results of this study show that the direct losses experienced by the community after the floods in January 2021 amounted to Rp.48,685,514.97. The indirect losses experienced by the community after the floods in January 2021 amounted to IDR 131,600,000. The total estimated loss experienced by households is IDR 180,254,514.97. The community knows that the house they live in is a flood-prone area, as a result of the flood some of the community's houses have become dirty with silt and garbage carried by the flood.